Engineering Pt/carbon-nanofibers/carbon-paper composite towards highly efficient catalyst for hydrogen evolution from liquid organic hydride. (28th September 2015) - Li, Xing; Tuo, Yongxiao; Jiang, Hao; Duan, Xuezhi; Yu, Xinhai; Li, Ping
Abstract Three kinds of structured carbon-nanofibers/carbon-paper (CNFs/CP) composites were synthesized through in-situ growth of CNFs on the surface of CP by catalytic chemical vapor deposition, and directly employed as the catalytic supports to disperse active Pt nano-particles for decalin dehydrogenation to produce COx-free hydrogen. The CNFs/CP composites combined the unique physico-chemical properties of CNFs and the excellent thermal conductivity and the large geometric surface area of CP, making them favorable for heat transfer to the strongly endothermic dehydrogenation reaction. The reaction and composite variables such as the feed volume and the CNF yield were optimized for pursuing the maximum amount of hydrogen evolution in a definite reaction time. The effects of morphology, texture property and microstructure as well as surface chemistry of CNFs of different CNFs/CP composites on the catalytic performance were investigated. The results show that the largest accumulative hydrogen amount (4.32 mol/gPt) in 2 h was generated from a proper volume of decalin over a novel structured Pt/CNFs/CP catalyst, which was fabricated with an appropriate growth of CNFs yielding 2.7 (wt./wt.) on CP via catalytic decomposition of CO gas over Fe particles.